ANALISIS PERAMPASAN ASET TANPA PUTUSAN PIDANA DALAM PENEGAKAN TINDAK PIDANA KORUPSI DI INDONESIA - Ganjar, Silawati Dayang (Ensiklopedia of Journal, 2025)
Abstract: Non-Criminal Asset Forfeiture allows the state to confiscate the proceeds of crime without waiting for a court decision. Because it is not strictly regulated in Indonesia's civil law system, asset recovery is often hampered.  To address this gap, the law on asset forfeiture was drafted to strengthen the effectiveness of law enforcement, particularly in corruption cases. This research raises two main problem formulations: (1) the urgency of regulating asset forfeiture without a criminal judgment in the Indonesian legal system; and (2) the effectiveness of implementing the mechanism for prosecuting corruption crimes. The research method used is normative jurisprudence, with a legislative approach and literature review. The results show that the Non-Criminal Asset Forfeiture regime is important for accelerating the process of recovering state assets and closing legal loopholes that perpetrators of corruption often exploit. Although there are challenges in its application, such as potential human rights violations, this mechanism can operate effectively with strict legal oversight and protection.Keywords: Asset Forfeiture, Corruption, Asset Forfeiture Bill.